THE STATE OF THE MARKETING MANAGEMENT PROFESSION IN THE PRESENT AND THE FUTURE - Abduraimov Muxammadabdullo (University Research Base, 2024)
Digital innovation, data analytics, and changing consumer behavior are all driving major changes in the marketing management field. This article examines the state of marketing management today, emphasizing important developments like omni-channel marketing, data-driven decision-making, digital transformation, and personalized customer experiences. It also looks at the opportunities and problems that marketing managers face, such as issues with data privacy, legal compliance, and technology disruption. The article explores the direction that marketing management will take going forward, projecting the continuous integration of immersive technologies, artificial intelligence, and new marketing paradigms. Marketers can steer their way through the changing terrain and propel long-term, sustainable growth for their companies by grasping these dynamics.